Facile one-pot in-situ synthesis of novel graphene oxide-cellulose nanocomposite for enhanced azo dye adsorption at optimized conditions. (15th October 2020) - Zaman, Aisha; Orasugh, Jonathan Tersur; Banerjee, Priya; Dutta, Soumyadip; Ali, Mir Sahidul; Das, Diphankar; Bhattacharya, Amartya; Chattopadhyay, Dipankar
Graphical abstract: Highlights: Facile one pot in situ synthesis of GO-cellulose nanocomposite. Application of modified Hummers' method directly for the synthesis of nanocomposite. 0.03 g L −1 of GOCNC yielded 98 % adsorptive removal of toxic dye methylene blue. Process is guided by both Langmuir and Freundlich isotherms. Novel adsorbent synthesis at low cost using waste jute as a source of cellulose. Abstract: This is the first report on utilization of modified Hummers' method for in-situ synthesis of novel graphene oxide-cellulose nanocrystals nanocomposite in a single reaction vessel. Cellulose used for nanocomposite preparation was extracted from waste jute. The synthesized nanocomposite was characterized with FTIR, XRD, SEM, EDX, DLS, and Zeta potential analyzer. It was applied as an adsorbent for the removal of toxic dye methylene blue from aqueous solutions. Around 98 % MB removal was achieved in 135 min. Under optimum experimental conditions recommended by response surface methodology, adsorption capacity of the nanocomposite was found to be 334.19 mg g −1 while the maximum adsorption capacity as determined by Langmuir isotherm 751.88 mg g −1 . Further analysis revealed that the process was guided by both Langmuir and Freundlich isotherm and followed pseudo-second-order kinetics. This cost-effective synthesis route and efficient adsorption capacity of the nanocomposite indicate its immense potential for large-scale application in wastewater treatment.